Family-school relationship and Down syndrome: perspectives of parents and teachers - Pereira-Silva, Nara Liana (2018)
This research explores the relationship between families with a son having Down syndrome (DS) and the school (F-S) from the point of view of the families and public school teachers in a city of Minas Gerais, Brazil. Two instruments were used: semi-structured interviews and a Checklist to characterize the daily shared routine and the relationship between F-S. For parents, the F-S link is evidenced in the parents-students relationship, while for teachers the F-S link is evidence in the parents-teachers relationship. In the interviews, parents indicate that the F-S relationship is fundamental to foster the development of skills for their children. Meanwhile, teachers consider the F-S relationship significant because it favors the schooling process for children with DS or intellectual disabilities, also adding challenges to establish schools with an inclusive approach.